THE USE OF TIKTOK AS A MARKETING COMMUNICATION STRATEGY MEDIA ON THE SHERIZ_OFFICIAL ACCOUNT: THE USE OF TIKTOK AS A MARKETING COMMUNICATION STRATEGY MEDIA ON THE SHERIZ_OFFICIAL ACCOUNT - Siti Nurima Septriyanti; Ririn Puspita Tutiasri; Irmawanti (JOSAR (Journal of Students Academic Research), 2023)
The shift in the function of the TikTok feature makes it very easy for business people to market their products. One business account that utilizes the function shift on TikTok is the @Sheriz_Official account. This study aims to determine how TikTok is utilized with the media marketing communication strategy on the @Sheriz_Official account. The theory used in this research is the Mediamorphosis Theory in cyberspace and the 7C Framework Theory to analyze how marketing communication strategies are applied to the @Sheriz_Official account. This research uses a descriptive qualitative approach with qualitative research methods. The data collection techniques used are in-depth interviews, observation, and documentation. The results of this study indicate that the shift in the function of TikTok social media, which gave birth to several business features, is beneficial for business people. The marketing communication strategies that are superior to the @Sheriz_Official account are regularly uploading TikTok video content every day, live streaming capit games, hyperlinking, TikTok Ads, brand community @Sheriz_Official, TikTok Shop, and TikTok Affiliates program. This research concludes that the function shift in the TikTok feature is very well utilized by the @Sheriz_Official account in implementing its marketing communication strategy.